Atomic Layer Deposition on Spray-Dried Supraparticles to Rationally Design Catalysts with Ultralow Noble Metal Loadings - Groppe, Philipp; Müller, Valentin; Will, Johannes; Zhou, Xin; Zhang, Kailun; Moritz, Michael; Papp, Christian; Libuda, Jörg; Retzer, Tanja; Spiecker, Erdmann; Bachmann, Julien; Mandel, Karl; et al. (Chemistry of Materials, 2025)
The controlled assembly of supraparticles by using spray-drying enables the synthesis of nanoporous materials. Changing the size of the constituent nanoparticles or their agglomeration states provides access to a diverse range of pore frameworks. This turns supraparticles into ideal scaffolds in heterogeneous catalysis. The combination of supraparticles with atomic layer deposition (ALD) as a surface functionalization technique offers excellent control over the deposition of a functional material and its distribution over the scaffold on the nanoscale. This work reports the combination of SiO2 supraparticles as tunable scaffolds and their loading with a platinum-based ALD catalyst. The deliberate adjustment of the scaffold pore framework via spray-drying and its effect on the catalyst deposition are highlighted. Furthermore, varying numbers of Pt ALD cycles are applied to explore the capability of the combination approach with respect to catalyst loading and Pt efficiency. High-resolution electron microscopy reveals ultrasmall Pt clusters deposited on the supraparticles after the very first ALD cycle. Using the hydrogenation of 4-nitrophenol as a demonstration, the impact of the pore framework and the Pt deposition variation in ALD on the catalytic functionality is investigated.
Created from Fastlane, Scopus look-up

Catalyst Supraparticles: Tuning the Structure of Spray-Dried Pt/SiO2 Supraparticles via Salt-Based Colloidal Manipulation to Control their Catalytic Performance - Groppe, Philipp; Reichstein, Jakob; Carl, Simon; Cuadrado Collados, Carlos; Niebuur, Bart Jan; Zhang, Kailun; Apeleo Zubiri, Benjamin; Libuda, Jörg; Kraus, Tobias; Retzer, Tanja; Thommes, Matthias; Spiecker, Erdmann; et al. (Small, 2024)
The structure of supraparticles (SPs) is a key parameter for achieving advanced functionalities arising from the combination of different nanoparticle (NP) types in one hierarchical entity. However, whenever a droplet-assisted forced assembly approach is used, e.g., spray-drying, the achievable structure is limited by the inherent drying phenomena of the method. In particular, mixed NP dispersions of differently sized colloids are heavily affected by segregation during the assembly. Herein, the influence of the colloidal arrangement of Pt and SiO2 NPs within a single supraparticulate entity is investigated. A salt-based electrostatic manipulation approach of the utilized NPs is proposed to customize the structure of spray-dried Pt/SiO2 SPs. By this, size-dependent separation phenomena of NPs during solvent evaporation, that limit the catalytic performance in the reduction of 4-nitrophenol, are overcome by achieving even Pt NP distribution. Additionally, the textural properties (pore size and distribution) of the SiO2 pore framework are altered to improve the mass transfer within the material leading to increased catalytic activity. The suggested strategy demonstrates a powerful, material-independent, and universally applicable approach to deliberately customize the structure and functionality of multi-component SP systems. This opens up new ways of colloidal material combinations and structural designs in droplet-assisted forced assembly approaches like spray-drying.
CRIS-Team Scopus Importer:2024-05-10
Keywords: catalysis; porosity; spray-drying; structure control; supraparticles

Core-Satellite Supraparticles to Ballistically Stamp Nanostructures on Surfaces - Oppmann, Maximilian; Miller, Franziska; Thuerauf, Sandra; Groppe, Philipp; Prieschl, Johannes; Stauch, Claudia; Mandel, Karl (ACS Applied Materials and Interfaces, 2018)
Nanostructured surfaces are of great importance in a very wide range of fields. They can be obtained by imprint or deposition techniques. However, these are usually sophisticated to perform. Generally, it is not easy to equip an object/product with a nanostructure after manufacturing. Yet, it would be very beneficial to achieve a modification of an arbitrary surface with a nanostructure of choice at a later stage by an approach that is simple to perform without the need of sophisticated equipment or excessive treatment by physicochemical methods. Herein, such a process is reported, which combines two "old-fashioned" techniques, namely, sandblasting and rubber-stamping, and translates them to the "nanoworld". By creating core-satellite supraparticles via spray-drying, a ballistic core-satellite stamp particle system is obtained, which can be used to easily transfer a wide range of nanoparticles to a great variety of surfaces to equip these with a nanostructure and subsequently advanced properties. These include water-repellant, antifouling, or antidust surfaces. Moreover, it is also demonstrated that the approach can be used to manufacture well-defined nanoimprinted surfaces. Such surfaces showed an improved spreading behavior for aliphatic alcohols, thus making such surfaces, for instance, very susceptible for disinfectants. All in all, the simple technique described herein has a great potential for creating nanostructured surfaces on nearly any surface.
CRIS-Team Scopus Importer:2020-04-02
Keywords: coatings; imprint; nanostructures; sandblasting; supraparticles; surface modification

Influence of cation concentration and valence on the structure and texture of spray-dried supraparticles from colloidal silica dispersions - Zhou, Huanhuan; Groppe, Philipp; Zimmermann, Thomas; Wintzheimer, Susanne; Mandel, Karl (Journal of Colloid and Interface Science, 2024)
The structure and texture of supraparticles determine their properties and performance, thus playing a critical role in research studies as well as industrial applications. The addition of salts is a well-known strategy to manipulate the colloidal stability of nanoparticles. In this study, this approach is used to tune the structure of spray-dried supraparticles. Three different salts (NaCl, CaCl2, and AlCl3) were added to binary silica (SiO2) nanoparticle dispersions (of 40 and 400 nm in size) to change their colloidal stability by lowering the electrostatic repulsion or enhancing the cation bridging. Dependent on the cation valence of the added salt and the nanoparticle size, the critical salt concentration, which yields nanoparticle agglomeration, is reached at different salt amounts. This phenomenon is exploited to tune the final structure of supraparticles - obtained by spray-drying binary dispersions - from core-shell to Janus-like to well-mixed structures. This consequently also tunes textural properties, like surface roughness and the pore system of the obtained supraparticles. Our results provide insights for controlling the structure of spray-dried supraparticles by manipulating the stability of binary nanoparticle dispersions, and they establish a framework for composite particle design.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Binary dispersions; Cation valence; Porosity; Silica; Spray-drying; Supraparticles

Luminescent Supraparticles Based on CaF2-Nanoparticle Building Blocks as Code Objects with Unique IDs - Miller, Franziska; Wintzheimer, Susanne; Reuter, Tim; Groppe, Philipp; Prieschl, Johannes; Retter, Marion; Mandel, Karl (ACS Applied Nano Materials, 2020)
In the course of globalization, tracking of material supply chains and product protection against counterfeiting is a topic of increasing relevance. The labeling of raw materials or product components with encoded microstructures may therefore ensure their reliable and tamper-proof identification. In this work, luminescent lanthanide doped calcium fluoride nanoparticles with characteristic optical properties are assembled to micrometer-sized supraparticles via spray-drying. By wise selection of these nanoscale building blocks, it is possible to create spectrally encoded microparticles. Their code relies on the relative emission intensities of the different luminescent nanoparticles and their concentration ratios within the supraparticle. Due to this strategy, we offer a nanoscale modular approach for an easily adjustable and simple creation of ratiometric luminescence-encoded microparticles for the tamper-proof marking of objects.
CRIS-Team Scopus Importer:2020-04-02
Keywords: luminescent code; marker; nanoparticle assembly; rare earth doped nanoparticles; supraparticle

Magnetic polyamide 11 powder for the powder bed fusion process by liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Groppe, Philipp; Granath, Tim; Düsenberg, Björn; Mandel, Karl; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2024)
Herein, we demonstrate the preparation of magnetic polyamide 11 feedstock powders for powder bed fusion (PBF) using liquid-liquid phase separation and crystallization. By adding magnetic nanomaterials during the precipitation process, the particulate additive is incorporated into the polymer matrix. This enables the production of filled systems at single particle level, which is advantageous in terms of the adjustable magnetic strength and homogeneity of the powder. Thermogravimetric analysis is used to determine the additive content and onset temperature of decomposition of composite powders, where additive-enhancement of PA11 powders with magnetic iron oxide nanoparticles showed a positive influence on the thermal stability of the feedstock. Successive analysis of particle size distribution, shape, colour, crystal structure, magnetic properties and thermal properties of the composite powders are carried out and their properties are discussed with respect to the PBF process. A decrease in particle size, width of the thermal process window and isothermal crystallization time can be attributed to the nucleating effect of the magnetic additive. The PBF processability of the composite feedstock is demonstrated by the production of magnetic tensile bar specimens from additive-enhanced PA11 powders with 1 wt.-% magnetic iron oxide.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Magnets; Nanocomposites; Polymer precipitation; Powder bed fusion; Powder characterization

Magnetizing Polymer Particles with a Solvent-Free Single Stage Process Using Superparamagnetic Iron Oxide Nanoparticles (SPION)s - Düsenberg, Björn; Groppe, Philipp; Müssig, Stephan; Schmidt, Jochen; Bück, Andreas (Polymers, 2022)
Magnetic polymer composites are used in a variety of applications in many industries. Their production methods are usually time-consuming and solvent-intensive as they are performed in liquid phase processes, such as emulsion polymerization or precipitation. In this work, a quick, easy, and solvent-free method is presented to coat polymer particles with a discrete, non-coherent coating of superparamagnetic nanoparticles. The results of the dry coating process are evaluated optically, by means of scanning electron microscopy (SEM), via powder X-ray diffraction and thermally by means of differential scanning calorimetry, before finally demonstrating the effectiveness of dry coating by means of a vibrating sample magnetometer<br

Molecular and Structural Insights into H2 Indicator Supraparticles: Lowering the Limit of Detection by Tuning Incorporated Catalyst Nanoparticles - Zhang, Kailun; Reichstein, Jakob; Groppe, Philipp; Schötz, Simon; Stockinger, Nina; Libuda, Jörg; Mandel, Karl; Wintzheimer, Susanne; Retzer, Tanja (Chemistry of Materials, 2023)
With the increasing interest in H2-based energy storage, H2 detectors gain significant importance. Here, we report on safe, i.e., spark-free, reliable, and highly reactive gasochromic H2 indicator supraparticles (SPs). They are assembled from different types of noble metal nanoparticles (NPs), SiO2 NPs, and the dye resazurin via spray-drying. Their sensing principle is based on the adsorption and activation of H2 on catalytically active noble metal NPs incorporated in the mesoporous supraparticulate framework. Upon stepwise hydrogenation of resazurin molecules with molecular mobility via activated H species, the indicator displays a fast color change visible to the naked eye. We investigate the effect of incorporating different catalytically active NPs into indicator SPs on their sensor performance at different H2 concentrations. We find that the size and material of the catalyst NPs have a strong influence on the sensor response of the H2 indicator as it changes the amount of activated H species available in the system. Enhancing the amount of interstitial H2O in the mesopores of the SPs increases their reaction volume but impairs the reproducibility of their sensor response. Among the studied materials, dispersed Pt NP-containing SPs give the overall best results in terms of overall performance toward H2 detection.<br

Nanoparticle Clustering in Supraparticles to Control Magnetic Long-Range Interactions - Wolf, Andreas; Zhou, Huanhuan; Groppe, Philipp; Stiegler, Lisa; Kämäräinen, Tero; Peukert, Wolfgang; Walter, Johannes; Wintzheimer, Susanne; Mandel, Karl (Particle & Particle Systems Characterization, 2024)
To tailor superparamagnetic iron oxide nanoparticles (SPIONs) to the specific needs of diverse application fields, it is essential to understand not only their intrinsic properties but also their interactions with each other. Theoretical models predicting/explaining the magnetization behavior of macroscopic samples containing millions of SPIONs are intricate due to the complexity of the underlying relaxation mechanisms in alternating fields. This study introduces supraparticles (SPs) as model architectures to empirically investigate magnetic interactions within and between large SPION clusters (>100 nanoparticles (NPs)). For this purpose, NP dispersions containing SPIONs and silica (SiO2)NPs as non-magnetic building blocks are spray-dried to form binary SPs. Selective salt-induced agglomeration of the two building block types before spray-drying is utilized to tailor SP architectures, including control over SPION cluster size, shape, and proximity. Magnetic particle spectroscopy (MPS), operating under ambient conditions, reveals altered magnetization behavior for different cluster structures. Not only the nearest SPION neighbors, but the whole cluster structure up to several micrometers is decisive for the magnetization behavior. This highlights the importance of long-range magnetic interactions. This work presents a versatile approach for designing model architectures to advance empirical interaction studies between SPIONs in macroscopic samples.
Created from Fastlane, Scopus look-up
Keywords: magnetic interactions; magnetic particle spectroscopy; selective agglomeration; spray-drying; superparamagnetic iron oxide nanoparticles; supraparticles

One-step fabrication of platelet-shaped Janus supraparticles via spray-drying - Zhou, Huanhuan; Prieschl, Johannes; Groppe, Philipp; Mandel, Karl; Wintzheimer, Susanne (Powder Technology, 2024)
Supraparticles, i.e. assemblies of nanoparticles, can be classified as Janus supraparticles if they comprise two different types of nanoparticles that are asymmetrically distributed within the supraparticles. Due to their anisotropic character, they exhibit a high potential for various applications. However, the development of a scalable and material-wise flexible method to fabricate Janus supraparticles is still a challenge. In this work, a one-step synthesis of Janus supraparticles via spray-drying is reported. The segregation of binary particle dispersions during droplet evaporation, the tunable hollowness of supraparticles, and their fragmentation due to mechanical forces in the cyclone are exploited to fabricate platelet-shaped Janus supraparticles. By varying cyclone types, weight and diameter ratio between large and small nanoparticles of binary dispersions, their solid content and ionic strength, an optimized parameter setting is achieved. The obtained understanding of how to fabricate Janus supraparticles from binary silica model dispersions is transferred to mixed silica, iron oxide, titania and alumina supraparticles. This work opens a door for fabricating platelet-shaped Janus supraparticles in a fast and scalable manner.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Janus supraparticle; Nanoparticle segregation; Spray-drying; Supraparticle; Supraparticle fragmentation

Real-time monitoring of magnetic nanoparticle-assisted nanoplastic agglomeration and separation from water - Groppe, Philipp; Wintzheimer, Susanne; Eigen, Andreas; Gaß, Henrik; Halik, Marcus; Mandel, Karl (Environmental Science: Nano, 2022)
Nanoplastics are one of the main modern concerns in water pollution and are suspected to have severe negative impacts on their surrounding ecosystems. The use of superparamagnetic iron oxide nanoparticles (SPIONs) as remediation agents is a suggested approach to address this issue. Their nanoparticulate and switchable magnetic properties enable a homogeneous distribution while magnetic collectability is feasible. However, uncertainties regarding an incomplete collection from treated water remain, which would pose another environmental burden. Herein, the nanoplastic remediation approach via SPIONs is investigated by utilizing magnetic particle spectroscopy (MPS) as an advanced qualitative characterization method. This work focuses on the influence of concentration ratio and colloidal stability of nanoparticles on the overall remediation process. Herein, MPS enables the in situ real-time monitoring of the agglomeration events and illustrates that high colloidal stability of the SPIONs prevents the formation of large, destabilized agglomerates and thus their successful magnetic removal. Furthermore, it is shown that at high SPION concentrations, nanoparticle residuals are left in dispersion after collection of formed agglomerates, while at low concentrations nanoplastic leftovers are found. Colloidal stability and concentration-dependence of the agglomeration process are recognized as key aspects to focus on when developing future particle-based materials for nanoplastic remediation from water.
CRIS-Team WoS Importer:2022-06-17

Safety Through Visibility: Tracing Hydrogen in Colors with Highly Customizable and Flexibly Applicable Supraparticle Additives - Reichstein, Jakob; Groppe, Philipp; Stockinger, Nina; Cuadrado Collados, Carlos; Thommes, Matthias; Wintzheimer, Susanne; Mandel, Karl (Advanced Materials Technologies, 2024)
The flammability of H2-air mixtures demands timely detection and precise localization of H2 leakages to ensure safety and targeted maintenance measures in the anticipated hydrogen economy. Herein, H2 indicator supraparticles (SPs) are demonstrated that meet this demand by making H2 visible to the naked eye by a rapid (ir)reversible color change. Their toolbox-like manufacturing from SiO2 nanoparticles (NPs), Pt NPs, and indicator dye molecules via spray-drying allows for engineering their structure, texture, and detection performance by systematically tuning their composition. It is demonstrated that decreasing the SiO2 NP size, increasing the Pt NP concentration, and adjusting the amount of dye molecules improve the SPs’ response times. This opens up the option for multidimensional customization of their detection performance. Furthermore, the toolbox of H2 indicator SPs containing the established resazurin system is expanded to other indicator dyes, which makes a color change and reversibility of choice feasible. H2 indicator SPs meet many of the target characteristics for H2 detectors, e.g., low limit of detection, cycle stability, and high selectivity. Moreover, the SPs’ particulate nature allows for their flexible application as an additive, e.g., in coatings or clothing, which enables the detection and localization of H2 leakages in relevant application scenarios.
CRIS-Team Scopus Importer:2024-04-26
Keywords: hydrogen; hydrogen indicators; hydrogen sensors; nanoparticles; supraparticles

Supraparticles for naked‑eye H2 indication and monitoring: improving performance by variation of the catalyst nanoparticles - Zhang, Kailun; Schötz, Simon; Reichstein, Jakob; Groppe, Philipp; Stockinger, Nina; Wintzheimer, Susanne; Mandel, Karl; Libuda, Jörg; Retzer, Tanja (Journal of Chemical Physics, 2023)
The recent transition to H2-based energy storage demands reliable H2 sensors that allow for easy, fast, and reliable detection of leaks. Conventional H2 detectors are based on the changes of physical properties of H2 probes induced by subsurface H-atoms to a material such as electrical conductivity. Herein, we report on highly reactive gasochromic H2 detectors based on the adsorption of H2 on the material surface. We prepared supraparticles (SPs) containing different types of noble metal nanoparticles (NPs), silica NPs, and the dye resazurin by spray-drying and tested their performance for H2 detection. The material undergoes a distinct color change due to the hydrogenation of the purple resazurin to pink resorufin and, finally, colorless hydroresorufin. The stepwise transition is fast and visible to the naked eye. To further improve the performance of the sensor, we tested the reactivity of SPs with different catalytically active NPs by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We show that the choice of the NP catalyst has a pronounced effect on the response of the H2 indicator. In addition, we demonstrate that the performance depends on the size of the NPs. These effects are attributed to the availability of reactive H-atoms on the NP surface. Among the materials studied, Pt-containing SPs gave the best results for H2 detection.

Supraparticles for Sustainability - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl (Advanced Functional Materials, 2021)
The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle-based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so-called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy-rate-related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans “fundamental needs.” 3) Energy storage and conversion, as well as 4) catalysis enable the “basic comfort.” 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining “modern life comfort.” In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields.
CRIS-Team Scopus Importer:2021-02-05
Keywords: nanomaterials; nanoparticles; supraparticles; sustainability

Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up

Thermite Reactions within Liquid Gallium/Iron Oxide Supraparticles Triggered Via Induction Heating - Raczka, Theodor; Groppe, Philipp; Hurle, Katrin; Moritz, Michael; Papp, Christian; Mandel, Karl; Wintzheimer, Susanne (ACS Applied Nano Materials, 2025)
Thermite reactions are well-known for mixtures of aluminum and iron oxide. However, other reactive metals, such as gallium, were not studied in this application, and the use of induction as an external trigger for the thermite reaction has not been established. In this work, supraparticles of gallium and iron oxide nanoparticles were synthesized to combine a low melting point with inductive heating properties. The enabled thermite-like redox reactions generate temperatures up to 900 °C within seconds in an alternating magnetic field, tunable by the material’s gallium content. Induction heating profiles are thus significantly expanded and could be applied for targeted heat-on-demand.
CRIS-Team Scopus Importer:2025-05-23
Keywords: gallium nanoparticles; induction heating; iron oxide nanoparticles; spray-drying; supraparticles; thermite

Tuning the Morphology of Spray-Dried Supraparticles: Effects of Building Block Size and Concentration - Zhou, Huanhuan; Pujales Paradela, Rosa; Groppe, Philipp; Wintzheimer, Susanne; Mandel, Karl (Particle & Particle Systems Characterization, 2022)
Tuning the morphology of supraparticles can crucially influence their final properties and is, thus, important for their application in chemical, pharmaceutical, and food industries. The present study reveals how varied nanoparticle sizes, concentrations, and weight ratios in multicomponent dispersions influence the morphology of supraparticles assembled by these nanoparticle building blocks via spray-drying. In a droplet containing monodisperse nanoparticles, smaller nanoparticles form a coherent elastic shell due to lower cohesive forces. As the solvent enclosed in the shell evaporates less easily due to the narrow pores between the nanoparticles, this ultimately results in rather non-spherical supraparticles, while larger nanoparticles tend to yield spherical supraparticles. When small nanoparticles outweigh large ones in binary or trinary dispersions, the small nanoparticles form the outer shell that shrinks into a mushroom cap-like shape upon drying of the spray-droplet, while larger nanoparticles stay in the center of the droplet, resulting in non-spherical supraparticles. Furthermore, the findings give a more systematic insight into structures that potentially arise from multimodal-sized building blocks, thus, paving the way to tune the supraparticle morphology upon spray-drying, when working with more complex, multicomponent dispersions.
CRIS-Team WoS Importer:2022-09-23